TEXTBOOK: WORK BASED LEARNING (WBL) MODULE : Bachelor of Engineering Technology in Rail Transportation with Honours (BNT) - Mimi Faisyalini Ramli,; Zuraidah Ngadiron,; Mohd Eizzuddin Mahyeddin,; Muhamad Faiz Abd Latif,; Reventheran Ganasan,; Mustapha Kamil Omran, (2022)
Work Based Learning (WBL) Module addresses the courses that will be implemented during WBL for programme Bachelor of Engineering Technology in Rail Transportation with honours (BNT). The implementation of WBL is during final year of study with the duration of fourty-eight (48) weeks. There are five (5) courses will be implemented during WBL such as Safety Practices, Data Analytics, Maintenance Practices, Project Management and Quality Assurance. Furthermore, Bachelor’s Degree Project 1 and 2 will be conducted during WBL. This book represents the synopsis, course learning outcomes, course contents, assessment including templates and rubrics also references for each WBL subjects.